2012
DOI: 10.1111/jace.12143
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conducting Oxides: Electronic Structure–Property Relationship from Photoelectron Spectroscopy with in situ Sample Preparation

Abstract: The various applications of transparent conducting oxides (TCO), e.g., as electrodes in flat panel displays and solar cells or as low‐emissivity coatings have stimulated extensive research on their fabrication and properties. Recent experimental and theoretical studies of defect properties have considerably improved the understanding of the limitations of the electrical conductivity of both n‐ and p‐type transparent conductors and of the structural and electronic surface properties of the most important TCO ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 167 publications
(387 reference statements)
3
90
0
Order By: Relevance
“…It was also shown that surface treatments such as plasma or chemical oxidation led to marked decrease in the separation between the main peak and the satellite for commercial ITO thin film samples with an Sn doping level of 8.8 % which in their native state showed a satellite energy of 0.85 eV, corresponding to a carrier density of 8.8 × 10 20 cm −3 . Very similar results were obtained by Gassenbauer et al for 9.2 % Sn doped In 2 O 3 thin films deposited in situ in the photoemission system [75,179,206] by magnetron sputtering in a pure Ar atmosphere [120]. Both In 3d 5/2 and O 1s core lines were fitted with single and double plasmon loss satellites with respective satellite energies of 0.89 and 1.10 eV [56].…”
Section: Satellite Structure In Core Level Photoemission Of Doped Samsupporting
confidence: 84%
“…It was also shown that surface treatments such as plasma or chemical oxidation led to marked decrease in the separation between the main peak and the satellite for commercial ITO thin film samples with an Sn doping level of 8.8 % which in their native state showed a satellite energy of 0.85 eV, corresponding to a carrier density of 8.8 × 10 20 cm −3 . Very similar results were obtained by Gassenbauer et al for 9.2 % Sn doped In 2 O 3 thin films deposited in situ in the photoemission system [75,179,206] by magnetron sputtering in a pure Ar atmosphere [120]. Both In 3d 5/2 and O 1s core lines were fitted with single and double plasmon loss satellites with respective satellite energies of 0.89 and 1.10 eV [56].…”
Section: Satellite Structure In Core Level Photoemission Of Doped Samsupporting
confidence: 84%
“…The films were produced within the Darmstadt Integrated System for Materials Research (DAISY-MAT) [13]. The DAISY-MAT consists of several deposition chambers connected via an ultra-high vacuum distribution chamber to a photoelectron spectroscopy (PES) analysis chamber, enabling in situ XPS analysis of the deposited films without breaking vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…37 This system permits thin film deposition by magnetron sputtering and characterization via monochromatic XPS (Physical Electronics PHI5700, Al K α , hν = 1486.6 eV) without breaking vacuum. Binding energies are recorded with respect to the Fermi energy, which is calibrated using a sputter-cleaned Ag foil.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%